1949
DOI: 10.3171/jns.1949.6.2.0118
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Report of Spinal Cord Injuries in a Group Of World War II Patients

Abstract: N 'INETY-FOUR patients with penetrating wounds of the spine were observed and treated during the overseas period of their injuries. Two to 3 years later an inquiry was made concerning the American members of this group. The early records have been analyzed and viewed from the standpoint of the results that have rewarded efforts employed in care. Of the 94 patients, 69 were Americans and r were foreigners (mainly German prisoners). Follow-up reports were available in 56 of the American group. Under pertinent he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Based on data from 10 studies, CGSWSCI rate at the cervical level was 30% (315 of 1055), at the thoracic level was 49% (518 of 1055), and at the lumbosacral level was 21% (222 of 1055) [13,[17][18][19][20][21][22][23][24][25]. Of the cervical SCIs, two studies examining gunshot injuries to the cervical spine reported the rate of complete injury to be approximately 70% (46 of 66) [26,27]. Two studies with data on lumbosacral injuries resulting in cauda equina and conus medullaris syndrome reported a 70% (85 of 121) rate of incomplete injury [6,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on data from 10 studies, CGSWSCI rate at the cervical level was 30% (315 of 1055), at the thoracic level was 49% (518 of 1055), and at the lumbosacral level was 21% (222 of 1055) [13,[17][18][19][20][21][22][23][24][25]. Of the cervical SCIs, two studies examining gunshot injuries to the cervical spine reported the rate of complete injury to be approximately 70% (46 of 66) [26,27]. Two studies with data on lumbosacral injuries resulting in cauda equina and conus medullaris syndrome reported a 70% (85 of 121) rate of incomplete injury [6,12].…”
Section: Resultsmentioning
confidence: 99%
“…Later, during World War II, aggressive débridement, decompression, and intradural exploration was the favorable treatment option. Reports of up to 40% neurologic recovery with this management strategy were made; however, no nonoperative control data were available [12,22,27]. The accepted indication for operative intervention at the time was an incomplete lesion with static or progressive neurologic deficit and a complete lesion if there was any suspicion of the spinal cord being intact.…”
Section: Introductionmentioning
confidence: 99%
“…15,28,29,37,42 Previously unheard of results were being reported. In Pool's series 32 of 57 patients treated during the years 1943-1944, 35 underwent a laminectomy and 57% showed a marked neurological improvement, compared with 4.5% spontaneous improve- Fig.…”
Section: Historymentioning
confidence: 99%
“…3,11,[17][18][19] Most patients with GSW in the spine have complete spinal cord injury. 3 Some studies show that the location of the lesion determines the deficit, so that cervical lesions lead to complete neurological deficits in B70% of the cases, 20,21 whereas lesions of the cauda equina and at the lumbosacral level are incomplete in 70% of cases. 9,22 The main prognostic factor considered for recovery is the initial neurological status 23 -that is, patients with incomplete deficit have superior functional prognoses compared with those initially evaluated as presenting complete deficits.…”
Section: Introductionmentioning
confidence: 99%